A Call to Use the Multicomponent Exercise Tai Chi to Improve Recovery From COVID-19 and Long COVID - Juan Pablo Castro; Marie Kierkegaard; Manuel Zeitelhofer (Frontiers Media S.A., 2022)
Approximately 10% of all COVID patients develop long COVID symptoms, which may persist from 1 month up to longer than 1 year. Long COVID may affect any organ/system and manifest in a broad range of symptoms such as shortness of breath, post-exercise malaise, cognitive decline, chronic fatigue, gastrointestinal disorders, musculoskeletal pain and deterioration of mental health. In this context, health institutions struggle with resources to keep up with the prolonged rehabilitation for the increasing number of individuals affected by long COVID. Tai Chi is a multicomponent rehabilitation approach comprising correct breathing technique, balance and neuromuscular training as well as stress- and emotional management. In addition, practicing Tai Chi elicits the relaxation response and balances the autonomic nervous system thus regulating respiration, heart rate, blood pressure and vitality in general. Moreover, Tai Chi has been shown to increase lung capacity, improve cognitive status and mental health, and thereby even the quality of life in diseases such as chronic obstructive pulmonary disease (COPD). Hence, we advocate Tai Chi as potent and suitable rehabilitation tool for post-COVID-19-affected individuals.